Linkage of routinely collected NHS data to evaluate liaison mental health services: challenges and lessons learned - Elspeth Guthrie; Allan House; Chris Smith; Sam Relton; Daniel Romeu; Sonia Saraiva; Peter Trigwell; Robert West; Farag Shuweihdi; Mike Crawford; Matt Fossey; Jenny Hewison; et al. (NIHR Journals Library, 2024)
Background Liaison mental health services provide mental health care to patients in acute hospital settings. Evaluation of liaison services is challenging due to their heterogeneous organisation and delivery, high case throughput and varied patient case mix. We aimed to link routinely collected National Health Service data from secondary care settings, chosen for their service characteristics, to data from primary care to evaluate hospital-based liaison mental health services in England. Methods We planned to compare patients referred to hospital-based liaison services with comparable patients in the same hospital not referred to liaison services and comparable patients in hospitals without any liaison services. We designed and enacted a methodology to link data from: (1) Hospital Episode Statistics, a database controlled by the National Health Service Digital and (2) ResearchOne, a primary care database controlled by The Phoenix Partnership. Results Obtaining approvals for the steps prespecified in the methodological protocol took 907 days. Enactment following approvals took 385 days. Data supplied from Hospital Episode Statistics contained 181,063 patients from 6 hospitals (mean = 30,177, standard deviation = 28,875.86) who matched the inclusion and exclusion criteria. Data supplied from ResearchOne contained 33,666 (18.6%) of these patients from the 6 hospitals (mean = 5611, standard deviation = 5206.59). Discussion Time required for approvals and enactment was attributable to slowness of data handling processes within each data holder and to resolution of technical and organisational queries between them. Variation in number of patients for which data was supplied between databases and between hospitals was attributable to coding inconsistencies and to the limited intersection of patient populations between databases and variation in recording practices between hospitals. Conclusion Although it is technically feasible to link primary and secondary care data, the current system is challenging, complicated, unnecessarily bureaucratic, time consuming and costly. This limits the number of studies that could be conducted with these rich data sources. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number 13/58/08. Plain language summary Background Liaison mental health services are based in acute general hospitals and provide assessment and treatment for people who have both physical and mental health problems. Aim Our aim was to use routinely collected National Health Service data to find out whether general hospital patients referred to liaison mental health services have improved outcomes, compared with patients not referred to liaison services, and comparable patients in hospitals where there are no liaison services. The main outcomes were less time spent in hospital and fewer re-admissions to hospital following discharge. Method We tried to link data from routine National Health Service sources for hospital and primary care, to compare patients referred to liaison mental health services with similar people in each hospital who had not been referred, and similar people in hospitals without any liaison services at all. We planned to find out how long these people stayed in hospital, whether they were re-admitted and how much was their healthcare cost was. Results We experienced significant difficulties in being able to link the National Health Service data from the different organisations we approached. The whole process was extremely complex, and a delay in one part of the process resulted delays in other parts. We eventually had to abandon the research without obtaining any meaningful data, although the lessons we learnt will be useful for other researchers, so they can avoid experiencing similar problems. Conclusions Routinely collected National Health Service data from primary care and secondary care can be linked using the approaches we tried, but we were unable to complete the process within the time frame of the research programme, even with time extensions. Current processes need to be streamlined and standardised with designated clear response times for the different organisations.